Experience and Explanation: The Justification of Cognitive Claims in Theology - Van Huyssteen, J. Wentzel (Zygon, 1988)
Abstract. The justification of cognitive claims in theology can be dealt with adequately only if the epistemological issues of metaphorical reference, experiential adequacy, and explanatory progress are seen as crucial problems for the more encompassing problem of rationality in theology. In order to guarantee any claim to reality depiction the theologian will have to argue for a plausible theory of reference on the basis of interpreted religious experience. In this discussion important analogies between the rationality of theological theorizing and the rationality of science are revealed.